Spring framework interview guide : 200+ questions and answers - Karanam, Ranga; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2018)
"The Spring framework is the most popular Java framework ever. It continues to evolve with changing architectures. Spring Boot is one of the most popular Spring projects. Spring Boot is the most used Java framework to develop RESTful services and microservices. Preparing for a Spring Interview is tricky. There are a wide variety of Spring modules and Spring projects you need to recollect and be prepared to answer questions on.You'll need to get a good understanding of the new features of Spring and have a firm grasp of the concepts you've implemented in your projects. This course helps you prepare for Spring interviews with code examples covering 200+ Spring interview questions and answers on Spring, Spring Boot, Spring MVC, Spring JDBC, JPA, AOP, RESTful Services, and SOAP web services."--Resource description page.
Title from resource description page (Safari, viewed April 2, 2018).
Presenter, Ranga Karanam.
Keywords: Java (Computer program language); Application software -- Development; Web site development; Employment interviewing; Electronic books